Between Female Dialogics and Traces of Essentialism: Gender and Warfare in Christa Wolf's Major Writings - Sabine Wilke (Studies in 20th & 21st Century Literature, 1993)
The relationship between memory, writing, and the question of how we define ourselves as gendered subjects is at the center of Christa Wolf's work. Her literary production, starting in the late fifties with a rather naive and un-selfconscious love story, has undergone a dramatic shift. In her more recent texts, Wolf sets out to rewrite classical mythology to make us aware of those intersections in the history of Western civilization at which women were made economically and psychologically into objects. The present essay seeks to locate Christa Wolf's evolving conception of gender and warfare within the contemporary theoretical discussion on identity and the subject sketched briefly above. While of late there has been a wealth of studies into the construction of gender in particular works by Wolf, no scholarly contribution has yet addressed the range of answers regarding those questions in her overall oeuvre. I will argue that whereas Wolf's earlier works present a dialogic conception of gender, her later narratives more and more expound a notion of the essentially more peaceful female subject that is counterposed to the essentially warloving male. In these works "female subjectivity is taken to be capable of articulating itself fully in its radical otherness outside of male discourse," which seems to support ideas of an ontological essence of "woman."
Keywords: memory; writing; gendered; gender; define; self; ourselves; Christa Wolf; late fifties; 1950s; naive; un-selfconscious love story; love story; rewrite classical mythology; Cassandra; Kassandra; intersection; history of Western civilization; women; economically; psychologically; objects; warfare; concept; identity; construction of gender; oeuvre; dialogic; dialogic conception of gender; peaceful female; female; warloving male; male; female subjectivity; otherness; male discourse; ontological essence of woman